Fidelity protocol for the Action Success Knowledge (ASK) trial: a psychosocial intervention administered by speech and language therapists to prevent depression in people with post-stroke aphasia. Issue 5 (5th May 2019) - Carragher, Marcella; Ryan, Brooke; Worrall, Linda; Thomas, Shirley; Rose, Miranda; Simmons-Mackie, Nina; Khan, Asad; Hoffmann, Tammy C; Power, Emma; Togher, Leanne; Kneebone, Ian
Abstract : Introduction: Treatment fidelity is a complex, multifaceted evaluative process which refers to whether a studied intervention was delivered as intended. Monitoring and enhancing fidelity is one recommendation of the TiDIER (Template for Intervention Description and Replication) checklist, as fidelity can inform interpretation and conclusions drawn about treatment effects. Despite the methodological and translational benefits, fidelity strategies have been used inconsistently within health behaviour intervention studies; in particular, within aphasia intervention studies, reporting of fidelity remains relatively rare. This paper describes the development of a fidelity protocol for the Action Success Knowledge (ASK) study, a current cluster randomised trial investigating an early mood intervention for people with aphasia (a language disability caused by stroke). Methods and analysis: A novel fidelity protocol and tool was developed to monitor and enhance fidelity within the two arms (experimental treatment and attention control) of the ASK study. The ASK fidelity protocol was developed based on the National Institutes of Health Behaviour Change Consortium fidelity framework. Ethics and dissemination: The study protocol was approved by the Darling Downs Hospital and Health Service Human Research Ethics Committee in Queensland, Australia under the National Mutual Acceptance scheme of multicentre human research projects. Specific ethics approval was obtained for those participating sites who were not under the National Mutual Agreement at the time of application. The monitoring and ongoing conduct of the research project is in line with requirements under the National Mutual Acceptance. On completion of the trial, findings from the fidelity reviews will be disseminated via publications and conference presentations. Trial registration number: ACTRN12614000979651.